Improving Students’ Reading Comprehension on Narrative Text by Using Story Mapping Strategy - Sri Meilanti Potale; Sartin T. Miolo; Sri Agriyanti Mestari (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this research is to find out whether story mapping strategy can improve students' reading comprehension or not. The population of this research is students of class VIII of SMP Negeri 15 Gorontalo City and the sample of this research is class VIII-2 which amounted to 20 students. This study used a pre-experimental design with one group pre-test and post-test. The results of this study showed that the mean value of the pre-test was 13.85, and the mean value of the post-test was 18.1. In addition, the results of the research hypothesis found that Tcount > Tlist or 11.172 > 2.101. This means that the hypothesis (H1) of this study is accepted. The students were able to map the basic components of the story such as character, setting, problem, and problem solving. Therefore, it can be concluded that story mapping strategy can improve the reading comprehension of students in class V111-2 SMP Negeri 1 Kota Gorontalo.